Amyotrophic lateral sclerosis: moving towards a new classification system. Issue 11 (October 2016) - Al-Chalabi, Ammar; Hardiman, Orla; Kiernan, Matthew C; Chiò, Adriano; Rix-Brooks, Benjamin; van den Berg, Leonard H
Summary: Amyotrophic lateral sclerosis is a progressive adult-onset neurodegenerative disease that primarily affects upper and lower motor neurons, but also frontotemporal and other regions of the brain. The extent to which each neuronal population is affected varies between individuals. The subsequent patterns of disease progression form the basis of diagnostic criteria and phenotypic classification systems, with considerable overlap in the clinical terms used. This overlap can lead to confusion between diagnosis and phenotype. Formal classification systems such as the El Escorial criteria and the International Classification of Diseases are systematic approaches but they omit features that are important in clinical management, such as rate of progression, genetic basis, or functional effect. Therefore, many neurologists use informal classification approaches that might not be systematic, and could include, for example, anatomical descriptions such as flail-arm syndrome. A new strategy is needed to combine the benefits of a systematic approach to classification with the rich and varied phenotypic descriptions used in clinical practice.